Inhibitory effect of NBL1 on PDGF-BB-induced human PASMC proliferation through blockade of PDGFβ-p38MAPK pathway. Issue 4 (31st August 2016) - Cui, Chuanjue; Zhang, Hongliang; Guo, Lin-Na; Zhang, Xiaoling; Meng, Liukun; Pan, Xiangbin; Wei, Yingjie
Abstract : Pulmonary artery remodelling is a key feature in the pathological progress of pulmonary arterial hypertension (PAH). Moreover, excessive proliferation of pulmonary arterial smooth muscle cells (PASMCs) plays a critical role in the pathogenesis of pulmonary artery remodelling. Neuroblastoma suppressor of tumorigenicity 1 (NBL1) has been previously shown to induce growth inhibition in tumour cells. However, the effect of NBL1 in the regulation of human PASMC proliferation remains unclear. In cultured human PASMCs, we observed a dose-dependent inhibitory effect of NBL1 on platelet derived growth factor (PDGF)-BB-induced cell growth, DNA synthesis and proliferating cell nuclear antigen (PCNA) expression, as measured by MTS assay, 5-ethynil-2-deoxyuridine (EdU) analysis and western blots respectively. We also detected the expression and activities of cell-cycle positive regulators (cyclin D1, cyclin E, CDK2, CDK4 and CDK6) and negative regulators (p21 and p27) in human PASMCs by western blots and co-immuoprecipitation (IP). Our results show that NBL1-induced growth suppression is associated with the decreased activity of cyclin D1–CDK4 and the decreased phosphorylation of p27 in PDGF-BB-treated human PASMCs. By western blots using the phosphor-specific antibodies, we further demonstrated that NBL1 induced growth suppression is mediated by blockade of the up-stream PDGF-receptor β (PDGFRβ)-p38 mitogen-activated protein kinase (MAPK). In conclusion, our results suggest that NBL1 could inhibit PDGF-BB-induced human PASMC proliferation, and the underlying mechanism is associated with the decreased cyclin D1–CDK4 activity and up-regulated p27 by decreasing the phosphorylation of p27 via blockade of PDGFRβ-p38MAPK signal cascade. Our findings may provide a potential therapeutic target for PAH.